A new species of Bryconops (Characiformes: Iguanodectidae) from the Rio Tapajós basin, Brazil - Wingert, Juliana M.; Chuctaya, Junior; Malabarba, Luiz R. (Zootaxa, 2018)
A new species of Bryconops is described from upper rio Juruena drainage, rio Tapajós basin, Amazon basin, state of Mato Grosso, Brazil. The new species is hypothesized as belonging to the subgenus Creatochanes by presenting the posterior extension of maxilla reaching to the junction of second and third infraorbital bones, and the ventroposterior margin of second infraorbital forming a complete border with third infraorbital, resulting in the lack of a naked area between them. The new species is easily distinguished from other species of the subgenus Creatochanes by the color pattern of the caudal fin, which consists of the dorsal lobe conspicuously dark pigmented on its distal half and the ventral lobe dark gray pigmented along its ventral portion below the horizontal through the ventral margin of the caudal peduncle.